2023
DOI: 10.3390/toxics11060505
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and Mutagenic Effects of Particulate Matter from Domestic Activities

Abstract: People spend most of their time indoors, particularly in their houses where daily activities are carried out, enhancing particulate matter (PM) emissions with consequent adverse health impacts. This study intended to appraise the toxicological and mutagenic responses of particulate matter with a diameter less than 10 μm (PM10) released from cooking and ironing activities under different conditions. The cytotoxicity of the PM10 total organic extracts was tested in A549 cells using the WST-8 and the lactate dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Based on these results, OC concentrations of 12.5 and 25 µg/mL were selected for subsequent assays. These results are in line with our previous studies that showed concentration-dependent decreases in the viability of A549 cells upon exposure to PM 10 extracts obtained from emissions related to cooking and ironing activities [46], biomass burning [47], wood-burning appliances [48], and residential pellet combustion [49].…”
Section: Cytotoxicity Of Pm 10 Organic Extractssupporting
confidence: 93%
“…Based on these results, OC concentrations of 12.5 and 25 µg/mL were selected for subsequent assays. These results are in line with our previous studies that showed concentration-dependent decreases in the viability of A549 cells upon exposure to PM 10 extracts obtained from emissions related to cooking and ironing activities [46], biomass burning [47], wood-burning appliances [48], and residential pellet combustion [49].…”
Section: Cytotoxicity Of Pm 10 Organic Extractssupporting
confidence: 93%